Health education: Effects on classroom climate and physical activity - Efstathiou, Nicholas T; Risvas, Grigorios S; Theodoraki, Eleni-Maria M; Galanaki, Evangelia P.; Zampelas, Antonios D (Health Education Journal, 2016)
Objective:The objective of this study was to investigate the relationship between classroom psychological climate and the physical and sedentary behaviour of primary school students after the implementation of an innovative education programme regarding nutrition and physical activity.Design:Randomised controlled trial.Setting:Study participants were 729 students, aged 8?10?years, in the third and fourth grade of 30 public primary schools in the Athens Metropolitan Area.Methods:Students were randomly assigned to three study groups: an Intensive Intervention Group (IIG) that underwent an intensive nutrition and physical activity education programme delivered by specialised personnel and teachers, an Intervention Group (IG) that underwent a less intensive programme delivered by their regular teacher and a Control Group (CG) that received no instruction. Classroom Psychological Climate (CPC) was measured in all groups, and the data regarding physical activity and sedentary lifestyle habits, such as the time spent viewing TV or video games (screen time), were recorded.Results:Friction declined and satisfaction increased significantly after the intervention in the IG compared with the CG. There was no significant difference in physical activity and screen time between the groups. Daily screen time was positively associated with increased friction, which is a measure of conflicts between students in the school environment.Conclusion:A school nutrition and physical activity education programme was shown to decrease friction by decreasing daily screen time and increasing outdoor activities. These findings also suggest that teachers alone may be more effective in delivering optional health education programmes than specialised personnel and instructors.